Evaluation of the Toddler Family Development Activity Group - Selvie Nofriani Tansile; Finta Amalinda (Journal of Public Health and Pharmacy, 2023)
The government's effort to overcome growth and development problems in toddlers is to integrate activities for the Toddler Family Development (BKB), Integrated Service Post (Posyandu) and Early Childhood Education (PAUD). The condition of the activities of BKB, Posyandu and PAUD so far seems to run independently so that there is a need for policies to synergize them so that the educational goals of "Indonesian Children are Healthy, Smart, Have High Aspirations and Have Noble Morals" with a holistic dimension. The purpose of the study was to know the evaluation of the Toddler Family Development (BKB) activity group in Kapiroe Village in Palolo District, Sigi Regency. This type of research is a qualitative research to evaluate the group activities of Toddler Family Development (BKB) in Kapiroe Village in Palolo District, Sigi Regency with in-depth interviews with informants and documentation. The results showed that to evaluate the learning itself, if the scope of the family involved cadres, the evaluation was carried out by posyandu activities at the end of the month. The conclusion of this research has been an evaluation of self-learning in the scope of family involving cadres, the evaluation is carried out by posyandu activities at the end of the month. It is expected that government agencies in Kapiroe Village, Sigi Donggala Regency to collaborate more with health agencies, especially regarding KBK information.